CONFLICTS IN ISLAMIC JURISDICTION - Jaya Miharja (Al-IHKAM: Jurnal Hukum Keluarga Jurusan Ahwal al-Syakhshiyyah Fakultas Syariah IAIN Mataram, 2019)
An interesting and easily visible phenomenon in the study of Islamic law is the existence of several concepts in pairs, for example, the concepts of zahir and mind, muhkamat and mutasyabihat, qat'iy and zanni, reason and revelation, as well as idealists and realists and so on. The problem that can arise is how to understand and position these concepts proportionally. Because it cannot be denied that there are parties who see dichotomously the phenomena of the pairing concepts. Can we say that there is no dichotomy between the paired concepts? This was observed by Coulson, who was originally a serial lecture material at Chicago University, United States.